The future of smallholder farming in India: Some sustainability considerations - Bisht, Ishwari Singh; Rana, Jai Chand; Ahlawat, Sudhir Pal (MDPI, 2020)
The biodiverse, predominantly crop-livestock mixed-farming in India is key to ensuring resilience to climate change and sustainability of smallholder farming agroecologies. Farmers traditionally grow diverse crops as polyculture, and agriculture is mainly organic/biodynamic with spirituality in food systems deeply ingrained. Job-driven out-migration of rural youths, the family labor force, and globalization of contemporary food choices under corporate industrial agriculture both adversely affect sustainability of traditional farming landscapes and compromise the nutrition and health of rural farming communities. Besides documenting information on general agri-food system policy inputs, our paper presents the results of an exploratory study of four crucial community-level initiatives conducted in four distinct agroecological landscapes of India, aimed at bringing sustainability to traditional farming and food systems. The driving force for fundamental change in agri-food system, and in society, is the question of sustainability. The organic and local food movements are but specific phases of the larger, more fundamental sustainable agri-food movement. While it is very critical to increase farmer livelihood, it is even more important to increase overall rural economy. It was found that four important interventions viz. linking organic agriculture to community-supported agriculture (CSA) initiatives; linking small-holder farming to school meal (MDM) programmes; enhanced market access and value chain development for local agricultural produce; and creation of employment opportunities at community level for rural youths and reducing over-dependence of rural population on agriculture as source of income can make traditional farming more profitable and sustainable. The transition to more sustainable methods of farming by selling the farm produce “locally” helps both consumers and farmers alike and is considered a future strength of smallholder Indian agriculture.